2013
DOI: 10.3892/or.2013.2696
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of ERCC1 and RRM1 gene single-nucleotide polymorphisms for first-line platinum- and gemcitabine-based chemotherapy in non-small cell lung cancer patients

Abstract: Platinum-based chemotherapy with third generation drugs (such as gemcitabine) is an efficacious regimen of first-line treatment of patients with advanced, unresectable non-small cell lung cancer (NSCLC), without activating EGFR mutations. Mechanism of action of cytostatics are distortions in the DNA. ERCC1 and RRM1 are key proteins involved in the repair of DNA, thus, they may be responsible for the ineffectiveness of therapy. We investigated whether ERCC1 (19007C>T) and RRM1 (-37C>A) polymorphisms impact resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
2
26
1
Order By: Relevance
“…In addition, studies examining SNPs and clinical outcome of NSCLC showed contradictory data. The ERCC1 protein belongs to the nuclear excision repair complex and is involved in the repair of platinum-based induced interstrand and intrastrand cross-links (Mlak et al, 2013). A previous study indicated that the rs11615 polymorphism is associated with reduced ERCC1 mRNA expression and protein levels, which are associated with reduced repair capacity and survival time (Metzger et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, studies examining SNPs and clinical outcome of NSCLC showed contradictory data. The ERCC1 protein belongs to the nuclear excision repair complex and is involved in the repair of platinum-based induced interstrand and intrastrand cross-links (Mlak et al, 2013). A previous study indicated that the rs11615 polymorphism is associated with reduced ERCC1 mRNA expression and protein levels, which are associated with reduced repair capacity and survival time (Metzger et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Excision repair cross-complementation group 1 (ERCC1) is an endonuclease essential in the nucleotide excision repair pathway and plays a role in DNA repair capacity and cancer risk as well as the clinical outcome of cancer (Wang et al, 2005). Recently, several studies suggested that variants in ERCC1 influence the susceptibility to and prognosis of various cancers Mlak et al, 2013;Yang et al, 2013;De Dosso et al, 2013). Few studies have investigated the role of ERCC1 variants in the clinical outcome in NSCLC (Ozdemir et al, 2013;Mlak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERCC1 is located on chromosome 19q13.32, interacts with other NER proteins, and guides the 5'-incision activity of the NER pathway (Volker et al, 2001). Previous studies reported that the ERCC1 polymorphism is correlated with increased chemotherapeutic sensitivity and may be a prognostic marker for various cancers treated with chemotherapy (Mlak et al, 2013;Moxley et al, 2013;Rumiato et al, 2013). The association between the ERCC1 polymorphism and gastric cancer has been reported in several studies (Huang et al, 2008;Liang et al, 2010;Yin et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have suggested that ERCC1 and RRM1 may play a role in chemosensitivity and the clinical outcomes of NSCLC patients treated with platinum-based chemotherapy (Kotoula et al, 2012;Leng et al, 2012;Pesta et al, 2012;Mlak et al, 2013). However, few studies have investigated the effect of ERCC1 and RRM1 on the clinical outcome of NSCLC or the association between ERCC1 and RRM1 expression and clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%